2014
DOI: 10.1016/j.freeradbiomed.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic induces sustained impairment of skeletal muscle and muscle progenitor cell ultrastructure and bioenergetics

Abstract: Over 4 million individuals in the US, and over 140 million individuals worldwide, are exposed daily to arsenic-contaminated drinking water. Human exposures can range from below the current limit of 10 µg/L to over 1 mg/L, with 100 µg/L promoting disease in a large portion of those exposed. Although increased attention has recently been paid to myopathy following arsenic exposure, the pathogenic mechanisms underlying clinical symptoms remain poorly understood. This study tested the hypothesis that arsenic induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 38 publications
(77 reference statements)
3
36
0
2
Order By: Relevance
“…Interestingly, phosphorylation of proteins encoded by USMG5 is known to be upregulated by insulin in vivo in human skeletal cells (Meyer et al 2007). In addition, mice exposed to 100 μg/L arsenite for 5 weeks showed impaired muscle function and mitochondrial myopathy compared with controls (Ambrosio et al 2014). Confirmation, through fine mapping or sequencing as well as through functional analyses, is needed on the relevance of USMG5 to arsenic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, phosphorylation of proteins encoded by USMG5 is known to be upregulated by insulin in vivo in human skeletal cells (Meyer et al 2007). In addition, mice exposed to 100 μg/L arsenite for 5 weeks showed impaired muscle function and mitochondrial myopathy compared with controls (Ambrosio et al 2014). Confirmation, through fine mapping or sequencing as well as through functional analyses, is needed on the relevance of USMG5 to arsenic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…While human exposures to As(III) in drinking water ranges from negligible amounts to 1–4 mg/l, 100 μg/l is commonly accepted as a threshold for promoting a number of diseases and in dose ranging studies we found that this exposure was near maximal in promoting vascular tissue remodeling . Our previous studies have demonstrated that these exposure levels do not cause any signs of overt lethality or changes in weight gain . All studies were approved by the Institutional Animal Care and Use Committee of the University of Pittsburgh.…”
Section: Methodsmentioning
confidence: 90%
“…Low to moderate levels of arsenic in drinking water (10–250 ppb) cause remodeling of liver, vascular, and metabolic tissues in mice (Straub et al, 2008; Lemaire et al, 2011; Garciafigueroa et al, 2013; Ambrosio et al, 2014). In abdominal adipose tissue, arsenic exposure changed adipocyte phenotype and lipid storage capacity while also causing redistribution of fat to perivascular regions in skeletal muscle (Garciafigueroa et al, 2013).…”
Section: Resultsmentioning
confidence: 99%